Succession of Actinomycetes During Composting Proccess of Dairy-Farm Waste Investigated by Culture-Dependent and Independent Approaches - Mukhlissul Faatih; Jaka Widada; N. Ngadiman (Universitas Gadjah Mada, 2008)
Mesophilic, thermophilic, and maturation phases were recognized in composting proccess. Temperaturechanges influence the microbial communities in compost within composting proccess. Actinomycetes account for alarger part of compost microbial population. The aim of this research was to study succession of actinomycetescommunity during composting of dairy-farm waste investigated by culture-dependent and independentapproaches.In culture-independent method, the succession of actinomycetes community was analyzed by nestedpolymerasechain reaction of ribosomal intergenic spacer (nested-PCR RISA) using spesific primer F243 and primerR23S followed by a second PCR using primers F968 and R23S. In culture-dependent method actinomycetes fromcompost were isolated on selective media, starch-nitrate medium and humic-acid + vitamins medium. DNA ofactinomycetes was extracted and amplified by repetitive sequence-based PCR (rep-PCR) using primer BOXA1R. Thebanding patterns were used to generate dendrograms by UPGMA clustering with NTSYS program. Microcosmcontaining sterile rice-straw and water which is inoculated with each actinomycetes isolates was used for examiningthe ability of each isolate in rice-straw degradation.The experiment results showed that succession of both bacteria and actinomycetes was occured withincomposting proccess of dairy-farm waste. Analysed by culture-independent method revealed that the highestcommunity of compost’s bacteria was on mesophilic, thermophilic, and maturation phases, respectively. WhereasPCR-nested RISA resulted the highest population of actinomycetes was on thermophilic, maturation, and mesophilicphases, respectively. By culture-dependent method was obtained 29 actinomycetes isolates from mesophilic phase,23 isolates from thermophilic phase, and 19 isolates from maturation phase. Genetic diversity analysis of the obtainedisolates showed the presence of phylogenetic grouping on each phase of composting proccess. This result illustratedthe occurance of succession of actinomycetes community in compost. The ability of each isolates in rice-strawdegradation was different, and SnT9 isolate was found to be a promising rice-straw degrader.Keywords: succession, actinomycetes, composting, nested-PCR RISA, rep-PCR